The value of intraocular pressure asymmetry in diagnosing glaucoma - Williams, Alice L.; Gatla, Srinivas; Leiby, Benjamin E.; Fahmy, Iman; Biswas, Amitava; De Barros, Daniela M. [UNESP]; Ramakrishnan, Rengappa; Bhardwaj, Suruchi; Wright, Carrie; Dubey, Suneeta; Lynch, Jorge F.; Bayer, Atilla; et al. (Wolters Kluwer, 2013)
PURPOSE
Keywords: Diagnosis; Glaucoma; Intraocular pressure asymmetry; adult; aged; cataract; controlled study; disease association; eye examination; female; glaucoma; human; intraocular pressure; major clinical study; male; optic disk; optic nerve lesion; premedication; priority journal; racism; refraction error; retrospective study; risk factor; visual field defect; Adult; Aged; Aged, 80 and over; Female; Glaucoma, Open-Angle; Humans; Intraocular Pressure; Male; Middle Aged; Retrospective Studies; Risk Factors; Tonometry, Ocular